Kitab Al Awwal min Silsilah Al-Qawa’id Al-‘Arabiyyah Al-Muyassarah wa Tawzhifuhu fi Tanmiyati Al-Maharat An-Nahwiyah lada Thullab li Ghayri An-Nathiqiina Biha: The First Book of the “Al-Qawāʿid al-ʿArabiyyah al-Muyassarah” Series and Its Implementation in Developing Grammatical Skills among Non-Native Arabic Learners - Miftachul Huda (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2026)
This study examines the effectiveness of the first book in the Al-Qawāʿid Al-ʿArabiyyah Al-Muyassarah series as a medium for teaching Arabic grammar to non-native speakers. The research analyzes the book's content and methodology, emphasizing its gradual approach in presenting grammatical concepts from basic to advanced levels. The findings indicate that the book effectively facilitates understanding by simplifying linguistic difficulties, providing structured exercises, and integrating grammar with other language skills such as reading, writing, listening, and speaking. The study highlights key features such as a step-by-step grammatical explanation, diverse exercises, and contextual applications, making the learning process more interactive and functional. However, the study also notes the need for more interactive elements and practical exercises to enhance real-world language application. The research recommends further development of Arabic grammar teaching methodologies, incorporating modern technologies and practical exercises to improve students' linguistic competence. Future studies should explore the impact of such methodologies on students' overall language proficiency.